HIGH INFECTIVITY AND PATHOGENICITY OF INFLUENZA A PESTILENCE VIA AEROSOL AND DROPLET TRANSMISSION - D., Pro. Yocip D; Prof. Lenvron; Andrew P , Piley (International Journal of Multidisciplinary Research and Studies, 2021)
Influenza virus could also be transmitted through the respiratory route by inhalation of an aerosol of non-sedimenting droplets, or by deposition of sedimenting droplets within the upper tract. Whichever of those is that the predominant route for infection with the influenza virus has been subjecting to continuing debate, leading to detailed studies of aerosol versus droplet exposure. A decisive knowledge gap preventing a satisfying conclusion is an absence of a well-defined human dose-response model for the influenza virus. This study uses a hierarchical approach generalizing over twelve human challenge studies collected in a very literature search. the excellence is formed between aerosol and intranasal inoculation. The results indicate high infectivity via either route, but intranasal inoculation ends up in about 20 times lower infectivity than when the virus is delivered in an inhalable aerosol. A scenario study characterizing exposure to airborne virus near a coughing infected person during a room with little ventilation demonstrates that with these dose-response models the chances of infection by either aerosol or sedimenting droplets are approximately equal. Droplet transmission ends up in a rather higher illness risk thanks to the upper doses involved. Establishing a dose-response model for influenza provides a firm basis for studies of interventions reducing exposure to different classes of infectious particles. More studies are needed to clarify the role of various modes of transmission in other settings.